Review of Nietzsche and Levinas “After the Death of a Certain God”, Eds. Jill Stauffer, Bettina Bergo - Erlewine, Robert (Sophia, 2009)
This is a book review of Nietzsche and Levinas "After the Death of a Certain God," ed. Jill Stauffer and Bettina Bergo.